The Impact of Canadian Training Programs on Long Term Unemployed - Geehan, Randall; Swimmer, Gene (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1991)
The purpose of this paper is to develop an econometric model capable of correcting the selection bias resulting from any simple comparison between participants and non-participants to training programs. It also aims at estimating the incremental impact of three Canadian training programs aimed at the long term unemployed.